2008
DOI: 10.1300/j200v06n01_16
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words

Abstract: The impact of borderline personality disorder on family members of persons with BPD is articulated best by family members themselves. Despite an increase in research demonstrating more hopeful outcomes for the diagnosis, many mental health professionals remain unaware of recent advances in BPD treatments and therapies. This lack of awareness has dramatic consequences not only for patients, but for their families as well. This chapter describes the personal experiences of 12 family members with relatives with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 12 publications
4
28
0
Order By: Relevance
“…Parents of daughters diagnosed with BPD reported experiencing significant burden in multiple domains that include emotional and physical health problems and marital difficulties [10]. Qualitative studies have also highlighted the chronic and traumatic stress, burden, prolonged hopelessness, shrinking social support, and feelings of grief, guilt and distress experienced by relatives of individuals with BPD [1114]. One study has even suggested that greater knowledge of BPD is associated with increased family members’ burden, distress and depression [15], raising concerns about the source, accuracy and value of information family members receive abut BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of daughters diagnosed with BPD reported experiencing significant burden in multiple domains that include emotional and physical health problems and marital difficulties [10]. Qualitative studies have also highlighted the chronic and traumatic stress, burden, prolonged hopelessness, shrinking social support, and feelings of grief, guilt and distress experienced by relatives of individuals with BPD [1114]. One study has even suggested that greater knowledge of BPD is associated with increased family members’ burden, distress and depression [15], raising concerns about the source, accuracy and value of information family members receive abut BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the view that parents can cause their children to develop a personality disorder has largely fallen out of favour, many caregivers still identify stigma and prejudice as major sources of burden (Bauer et al, 2012). Similarly, family members have reported feeling blamed by mental health practitioners, who questioned the quality of the client's early upbringing (Buteau, Dawkins & Hoffman, 2008), or stigmatized and dismissed by mental health care staff (Dunne & Rogers, 2013). Some authors argue there is a unique and additional stigma associated with having BPD, above and beyond other mental illnesses, such that families experience surplus stigma when a member has BPD (Krawitz, Reeve, Hoffman, & Fruzzetti, 2016).…”
Section: Stigma Another Background Variable That May Be Related To Pmentioning
confidence: 99%
“…Clinicians' perceptions. Those caring for people with personality disorders have largely indicated dissatisfaction with their loved ones' clinicians and treatment (Bauer et al, 2012;Buteau et al, 2008;Dunne & Rogers, 2013;Goodman et al, 2011). There are a number of factors that may give rise to this frustration, including clinicians' negative perceptions of those with personality disorders.…”
Section: Problems With Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of living with a BPD relative, family members often experience an emotional and financial burden [13] and may blame themselves for their relative’s illness or for not being able to do more to help [12, 14]. This can lead to emotional pain including anxiety, guilt, anger, frustration, despair, and hopelessness [12, 13, 15]. …”
mentioning
confidence: 99%